WTO Law and Trade Policy Reform for Low-Carbon Technology Diffusion Common Concern of Humankind, Carbon Pricing, and Export Credit Support - Ahmad, Zaker (World Trade Institute Advanced Studies, 2021)
In WTO Law and Trade Policy Reform for Low-Carbon Technology Diffusion, Zaker Ahmad puts a spotlight on the crucial importance of dismantling market barriers and offering incentives to improve clean technology access and diffusion across borders. To that end, the author argues for a synergistic co-development of the international trade and climate legal regimes. Two case studies - one on carbon pricing, another on official export credit support - place the theoretical arguments in a practical trade policy setting. The emerging doctrine and principle of Common Concern of Humankind serves as the key theoretical and structural foundation of the work. A useful read for anyone interested in an effective role of trade law and policy to facilitate climate action. Readership: Policy professionals, and academics working on the issue of trade, climate change, and technology transfer are key readers. Also useful for anyone interested in the role of trade in service of climate mitigation.